Proceedings of the 2017 6th International Conference on Energy and Environmental Protection (ICEEP 2017) 2017
DOI: 10.2991/iceep-17.2017.203
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sintering temperature on the performance of IT-SOFC SrFe0.9Sb0.1O3- perovskite oxide

Abstract: Abstract. The perovskite cathode material of SrFe 0.9 Sb 0.1 O 3-δ (SFS) was prepared by glycine-nitrate process (GNP). The SFS oxides sintered at 1150,1200 and 1250 ºC for 10 h were crystallized into a single phase perovskite structure, respectively. The effect of sintering temperature on crystal structure, conductivity and polarization resistance was also discussed in detail. The X-ray diffraction and SEM results show that the density increases with the increase of sintering temperature. The results of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Therefore, there is always a tradeoff between the materials and the manufacturing process when determining the sintering temperature, and many studies have reported change of the electrode or cell performance outcomes according to the sintering temperature. 125,126 Surprisingly, however, none of these prior studies discussed how the sintering temperature affects the degree of Sr segregation and, thus, deterioration of electrode performance. Sintering takes place only for a short time within a few hours at higher temperatures while the operating temperature of the cell is relatively low but lasts for a very long time, possibly under a strong thermodynamic potential gradient.…”
Section: Other Contributions To Sr Segregationmentioning
confidence: 99%
“…Therefore, there is always a tradeoff between the materials and the manufacturing process when determining the sintering temperature, and many studies have reported change of the electrode or cell performance outcomes according to the sintering temperature. 125,126 Surprisingly, however, none of these prior studies discussed how the sintering temperature affects the degree of Sr segregation and, thus, deterioration of electrode performance. Sintering takes place only for a short time within a few hours at higher temperatures while the operating temperature of the cell is relatively low but lasts for a very long time, possibly under a strong thermodynamic potential gradient.…”
Section: Other Contributions To Sr Segregationmentioning
confidence: 99%